2012
DOI: 10.1021/ma202605n
|View full text |Cite
|
Sign up to set email alerts
|

Online Monitoring of Styrene Polymerization in Miniemulsion by Hyperpolarized129Xenon NMR Spectroscopy

Abstract: Online monitoring of a miniemulsion polymerization of styrene by hyperpolarized 129 Xe NMR spectroscopy is presented. The chemical shift of 129 Xe directly reports on the monomer/polymer ratio in the reaction mixture and therefore on the conversion of the reaction. The method allows for monitoring the progress of a polymerization with high time resolution and without sample extraction. The results obtained by 129 Xe NMR spectroscopy were successfully validated by comparison with results of calorimetry. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…This lifetime issue limits the application of hyperpolarization to the observation of sufficiently fast processes, e.g. fast chemical reactions 15,16 or metabolism pathways. [17][18][19] Thus, during the last few years, a lot of research was conducted to overcome this issue.…”
Section: Introductionmentioning
confidence: 99%
“…This lifetime issue limits the application of hyperpolarization to the observation of sufficiently fast processes, e.g. fast chemical reactions 15,16 or metabolism pathways. [17][18][19] Thus, during the last few years, a lot of research was conducted to overcome this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy appeared as one of the most promising spectroscopic methods because of its fast response, its very low sensitivity to water, its applicability to both homogeneous and heterogeneous reaction media and the relative easiness of its use both at the laboratory scale and in industrial environment . Other spectroscopic techniques like nuclear magnetic resonance or fluorescence have been reported for monitoring polymerization reactions either in homogenous or in heterogeneous reaction media but mainly at the laboratory scale. It has been shown that Raman spectroscopy allowed in situ determination of monomer consumption in free radical polymerization reactions carried out with different processes: several examples have been reported for bulk polymerization and emulsion polymerization while there is only one example for miniemulsion process .…”
Section: Introductionmentioning
confidence: 99%
“…[48] Zakharov and coworkers introduced in situ CT MAS NMR spectroscopy under continuous flow conditions to monitor the dynamics of propene polymerization over a supported Ziegler catalyst. [49] Landis and coworkers investigated the kinetics of the catalyst polymerization of 1-hexene by utilizing stopped-flow NMR spectroscopic measurements.…”
mentioning
confidence: 99%